If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 6) = 4x + -8 Reorder the terms: 3(6 + 2x) = 4x + -8 (6 * 3 + 2x * 3) = 4x + -8 (18 + 6x) = 4x + -8 Reorder the terms: 18 + 6x = -8 + 4x Solving 18 + 6x = -8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 18 + 6x + -4x = -8 + 4x + -4x Combine like terms: 6x + -4x = 2x 18 + 2x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 18 + 2x = -8 + 0 18 + 2x = -8 Add '-18' to each side of the equation. 18 + -18 + 2x = -8 + -18 Combine like terms: 18 + -18 = 0 0 + 2x = -8 + -18 2x = -8 + -18 Combine like terms: -8 + -18 = -26 2x = -26 Divide each side by '2'. x = -13 Simplifying x = -13
| z=2z+3z | | 252=45t | | 0.15x+3.45=46.5 | | -2(4n+4)=6 | | H=35t-16t^2 | | -3y+8=9 | | 15*3n= | | -1/7t9 | | 5(5x-2)=15 | | 4-9/5x5 | | 1.5x=16 | | P=2(62)+2(65) | | 4x-2z=3y | | 5d-(-3)=53 | | 8x+7-y=38 | | y=9x^2+18*x-6 | | 5p+(3p-20)=180 | | 7=x/2-5 | | 5d-(-3)=52 | | -x-23=5x | | 93=16-5x | | (10x-4)(x+1)=0 | | -4(v-2)=-6n+34 | | 2(4w+10)*3=6 | | 3v+36=-6v | | 3ab+6ba= | | 2(x+3)-(6x-1)=8x-17 | | (33-q)+(3q+5)=90 | | 4x+2-7=0 | | 0=3x^5-5x^4-25x^3+25x^2+2x-3 | | -y=-7y-36 | | -6(2t+7)=-114 |